Pemanfaatan Daun Lamtoro Dengan Penambahan Cucian Air Beras dan Urine Sapi Untuk Pembuatan Pupuk Organik Cair - Sawitri, Niken, Dra. Aminah Asngad, M. Si (2016)
Organic fertilizer Is a result of deterioration from organic things that is from the rest of the plant, animal waste and human. Extract Leuceaena, the water washing rice and urine a broomcan be combined to get product of liquid organic fertilizer that contains nitrogen, phosphorus and potassium.The purpose of this research to know the content of N and P in liquid organic fertilizer of extract Leucaena leaves, the water washing rice, and cow's urine. The method of this research is completely randomized design (RAL) with two factors, the frist factor 1: concentration of the extract of the leaves of leucaena and water washing rice 168 ml: 82 ml (K1), 125 ml:125 ml (K2), 82 ml: 168 ml (K3)and factor 2 : urine a broom75 ml (I1), 80 ml (I2), 85 ml (I3). This research is from the best dose of the treatment K1I3 (Leucaena 168 ml: the water washing rice82ml, urine a broom85ml) that is 0,55%. While phosphorus is found in the highest treatment K2I3 (extract leucena leaves 125ml : the water washing rice125ml and urine a broom85ml) are 90.80 ppm. The conclusionsuggests that the influence of leucaena leaf extract , the water washing rice against the element nitrogen and phosphorus